APPLICATION OF ARTIFICIAL INTELLIGENCE IN E-LEARNING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article examines the control and evaluation of students' knowledge, with the aim of determining and analyzing the mistakes made and their prevention in order to achieve a better education. The role of electronic tests as a preferred and applied means of knowledge assessment is shown. Emphasis is placed on the application of artificial intelligence as an assistant to the learner for the rapid elimination of gaps and assimilation of knowledge, when weaker results are reported on electronic tests in a given academic discipline.